2022
DOI: 10.1177/10436596221107601
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maternal Adjustment Enhancement Program Using Mobile-Based Education for Chinese Immigrant Women in Korea: A Quasi-Experimental Study

Abstract: Introduction: This study aimed to develop a maternal adjustment program for Chinese immigrant primiparous women in Korea and to investigate its effectiveness. Methodology: Forty-five Chinese immigrant women with newborns were recruited and conveniently assigned into experimental and control groups. A maternal adjustment enhancement program was initiated to the experimental group using a mobile-based education regarding cultural intimacy for 4 weeks. Results: In the follow-ups, the experimental group showed sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Thus, the intervention programme's long-term effect should be assessed in the future. By contrast, a recent study reported that a mobile phone-based education intervention can reduce childcare stress and improve social support; however, this study included only immigrant Chinese women with newborn babies ( Song et al, 2022 ). Our study participants included mothers of preschool children aged 0–6 years and who were relatively diverse.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, the intervention programme's long-term effect should be assessed in the future. By contrast, a recent study reported that a mobile phone-based education intervention can reduce childcare stress and improve social support; however, this study included only immigrant Chinese women with newborn babies ( Song et al, 2022 ). Our study participants included mothers of preschool children aged 0–6 years and who were relatively diverse.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, Internet-based interventions may be a possible approach to reducing stress, anxiety, and depression in prenatal women ( Bright et al, 2022 ). Among immigrant Chinese women, Internet-based information resources have been widely desired ( Gong & Bharj, 2022 ), and an Internet-based education programme can help increase their social support and decrease parenting stress ( Song et al, 2022 ). However, Internet-based interventions to improve mental health are still lacking.…”
Section: Introductionmentioning
confidence: 99%